Defects of Tensioned Membrane Structures in the Tropics - Wang, C.; Abdul-Rahman, H.; Wood, L.C.; Mohd-Rahim, F.A.; Zainon, N.; Saputri, E. (American Society of Civil Engineers, 2015)
The wide use of tensioned membrane structures (TMS) is prominent in many designs because of its aesthetic, ergonomic, and economical nature. Recently, TMS has been applied in the tropics with success, yet defects specific to this region have received little attention. Through a questionnaire survey of 890 users and technicians of TMS in three different areas in Malaysia, this study identified the most frequently occurring TMS defects in the tropics, such as "deterioration of roof coatings," "corrosion or fatigue in fixings," "fungal decay, mold growth, and dirt in membrane," "corrosion in anchor cables," and "degradation of fabrics." These defects are quite different from those in other climatic zones. The top five causes of TMS defects in the tropics are weather, aging, design, construction/installation, and material selection. However, only "corrosion or fatigue in fixings" is a significant predictor for "deterioration of roof coatings." While this is not a causal effect, a practical implication is that TMS maintenance workers do not have to climb up to the roof to check the deterioration in coating but only need to predict the deterioration through the corrosion levels of the fixings. Further, seven countermeasures for TMS defects in the tropics are recommended. This study is the first comprehensive study examining tensioned membrane structure defects in the tropics.